1977
DOI: 10.1093/infdis/135.3.358
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Pox Disease among Carnivora (Felidae) and Edentata

Abstract: An outbreak of pox disease in Carnivora of the family Felidae occurred in the Moscow Zoo. Two forms of the disease were found: (1) fatal, fulminant pulmonary without skin lesions and (2) dermal with rash. The severity of the dermal form varied from subclinical to lethal. The pulmonary form was characterized by pneumonia and exudative pleuritis, and large concentrations of virus were observed in the lungs and exudate. In addition to Carnivora of the family Felidae, two giant anteaters had a severe form of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
7

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 3 publications
2
51
1
7
Order By: Relevance
“…In recent years cowpox virus and unclassified orthopoxviruses closely related to it have caused serious infections in valuable captive animals, notably okapis (Zwart, Gispen & Peters, 1971), lions, cheetahs, pumas, jaguars, panthers (Marennikova et al 1977), and elephants (Baxby & Ghaboosi, 1977). We report here virological, serological and epidemiological aspects of an outbreak of cowpox in cheetahs (Acinonyxjubatus) at the Zoological Society of London's Whipsnade Park in February 1977.…”
Section: Introductionmentioning
confidence: 94%
“…In recent years cowpox virus and unclassified orthopoxviruses closely related to it have caused serious infections in valuable captive animals, notably okapis (Zwart, Gispen & Peters, 1971), lions, cheetahs, pumas, jaguars, panthers (Marennikova et al 1977), and elephants (Baxby & Ghaboosi, 1977). We report here virological, serological and epidemiological aspects of an outbreak of cowpox in cheetahs (Acinonyxjubatus) at the Zoological Society of London's Whipsnade Park in February 1977.…”
Section: Introductionmentioning
confidence: 94%
“…The first serological evidence of rodent hosts for CPXV was established in Russia (Marennikova et al 1977) in a retrospective study that showed Wistar rats to be the source of CPXV infections of several animals and humans in the Moscow zoo. The primary route of human infection is via bites of rats or other rodent species or by skin contacts with infected domestic animals that carry the pathogen from the original rodent hosts (Marennnikova et al 1988, Postma et al 1991, Lewis-Jones et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we cannot but pay attention to the similarity of the clinical picture with that seen in the person who handled the sick carnivora during the outbreak in the zoo caused by the same virus (Marennikova, Maltseva, Korneeva & Garanina, 1977 …”
Section: Discussionmentioning
confidence: 97%